Politik Hukum KUHP dan KUHAP Baru di Indonesia: Analisis Supremasi Hukum, Kebebasan Sipil, dan Ketegangan Kekuasaan dalam Demokrasi Kontemporer - Chens Melody (Perkara : Jurnal Ilmu Hukum dan Politik, 2025)
This study analyzes legal politics in the reform of the Indonesian Penal Code (KUHP) and Criminal Procedure Code (KUHAP), focusing on its implications for the rule of law, civil liberties, and power relations in contemporary democracy. The study is grounded in public and academic debates concerning tensions between strengthening state authority and protecting citizens’ rights within a democratic rule-of-law framework. Using a qualitative empirical legal approach, data were collected through in-depth interviews and focus group discussions (FGDs) with 20 informants, including legal academics, practitioners, law enforcement officers, and civil society representatives. The data were analyzed thematically to identify dominant perceptions and issues surrounding the reforms. The findings reveal that civil liberties emerged as the most dominant concern, followed by the rule of law and power relations in the criminal justice system. Although the reforms are perceived as efforts to strengthen and unify the national legal system, several provisions are considered potentially problematic due to legal uncertainty and imbalances in authority. This study contributes to the discourse on criminal law politics and offers recommendations for ensuring that future legal reforms remain consistent with democratic principles, human rights protection, and effective checks and balances.